2005
DOI: 10.1111/j.1600-0609.2005.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylation status of fragile histidine triad (FHIT) gene and its clinical impact on prognosis of patients with multiple myeloma

Abstract: Aberrant methylation of tumor suppressor genes (TSG) has been studied in multiple myeloma (MM). We determined the methylation status of the FHIT (fragile histidine triad) gene, a putative TSG, in 48 patients with MM. Clinical association with its methylation status was then analyzed. The FHIT gene methylation was observed in 21 of the 48 patients (44%). No association between FHIT gene methylation and clinical variables such as age, gender and clinical stage was found. However, the estimated 50% survival time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Our studies searched 9 studies which included 1077 patients. A number of studies showed that inactivation of FHIT can cause tumor aberrant progression and link to clinicopathological characteristics 27 48 49 50 51 . Therefore, FHIT can be considered as a tumor suppressor, and its inactivation could contribute tumor progression and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies searched 9 studies which included 1077 patients. A number of studies showed that inactivation of FHIT can cause tumor aberrant progression and link to clinicopathological characteristics 27 48 49 50 51 . Therefore, FHIT can be considered as a tumor suppressor, and its inactivation could contribute tumor progression and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“… 55 A number of studies showed that inactivation of FHIT can cause tumor aberrant progression and link to clinicopathological characteristics. 28 , 38 , 56 58 Therefore, FHIT can be considered as a tumor suppressor, and its inactivation could contribute to tumor progression and poor prognosis. Although only four studies evaluated the relationship between OS and FHIT hypermethylation in NSCLC, they showed very similar results.…”
Section: Discussionmentioning
confidence: 99%
“…In MM, DNA methylation is important for the pathogenesis, progression and prognosis of the disease. Previous studies have suggested that numerous genes are hypermethylated in MM, including glutathione peroxidase 3, retinol binding protein 1, secreted protein acidic and cysteine rich, transforming growth factor β induced, cyclin-dependent kinase inhibitor 2A, suppressor of cytokine signaling 1, fragile histidine triad 1, death associated protein kinase 1 and transforming growth factor β receptor 2 (34)(35)(36)(37)(38). Therefore, targeting DNA methylation may permit optimized therapy for MM, which warrants further investigation.…”
mentioning
confidence: 99%